Vicarious liability in Costa Rica: theory of created risk and its analysis compared to famous rulings of the Supreme Court of the United Kingdom and the Court of Appeals of New York - Rivera Araya, Jaime (2025)
The present commentary consists initially of a very summarized presentation of what is considered vicarious liability in our country, and how it has been interpreted under the “created risk theory” by the judicial precedents of the First Chamber of the Costa Rican Supreme Court of Justice.